(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Hypopharyngeal carcinoma is a major ENT problem day by day. No treatment is available yet with satisfactory outcome. Advanced stage of presentation makes the condition worse. But still some cases presenting at early stage have successful outcomes. So, it is essential to improve knowledge regarding socio-demographic variables, different risk factors, mode of presentation and burden of disease in the community of Hypopharyngeal carcinoma. Objectives: To determine the association of personal habits is in Hypopharyngeal carcinoma, observe the different socio- demographic variables of hypopharyngeal carcinoma, to see different risk factors of hypopharyngeal carcinoma and to observe different clinical symptoms associated with hypopharyngeal carcinoma. Study design: This was a cross sectional, descriptive type of observational study. Study place: study was conducted at department of Otolaryngology and Head& Neck surgery. Bangladesh Medical University (BMU) Period of study: Study duration was 1 year from 1st March 2023 to 28 February 2024. Sample size: Study was carried out with a sample size of 40. Methods: This cross sectional, observational study was conducted from 1st March 2023 to 28 February 2024 for duration of 1 year among the patients who admitted at department of Otolaryngology and Head& Neck surgery. Bangladesh Medical University. Purposive sampling method was used to collect data. Pre-tested structured data sheet was used to record information. After collection, data was edited by meticulous checking and re- checking. Data was analyzed using SPSS for windows version 22. Results: The results of this study showed that Hypopharyngeal carcinoma affects more if fifth (37.5%) and sixth (25%) decades of life. Males are highly predominant to develop Hypopharyngeal carcinoma. Male female ratio 5:1. People with low socio-economic status were found more affected by Hypopharyngeal carcinoma. In this observation smoking was found significantly associated with development Hypopharyngeal carcinoma. In this series 82% of patients had history of smoking with mean duration of smoking was 13.5 years. About 75% of patients presented palpable lymph nodes and most of them were at level 11(72%). Pyrifrom fossa is the commonest site (84%). In this study all the malignancy was histologically squamous cell carcinoma. Maximum patient presented at advanced stage (stage I and stage III). Conclusions: Carcinoma of hypopharynx affects more at advanced age. Due to indolent nature of the disease, it is usually present at advanced stage. So, care should be taken early diagnosis of Hypopharyngeal carcinoma. Journal of Paediatric Surgeons of Bangladesh (2025) Vol. 16 (1 & 2): 37-41